I think the sum must be exactly one. Here's why:
First, A(2n) = A(n) + 1 (multiplying a number by two in binary adds a
zero to the end so the digit count increases by exactly one).
Next, B(2n) = B(n) (we added a zero, so the 1 count is the same)
Also, A(2n+1) = A(n) + 1 (since multiplying by two added a zero on the
right, adding one changes the zero to a one with no change in digit
count)
And B(2n+1) = B(2n) + 1 (since this time we added a 1 on the right)
Now, let's define C(n) = A(n) + B(n). C(2n) = C(n) + 1 and C(2n+1) = C(n) + 2.
Consider two consecutive terms in the sequence where the first term has
n even. These must be (1/2)^C(2n) + (1/2)^C(2n+1) for some n, which is
equal to (1/2)^(C(n) + 1) + (1/2)^(C(n)+2) = (1/2)(1/2)^C(n) +
(1/4)(1/2)^C(n) = (3/4)(1/2)^C(n).
This is true for all n, so the entire sum S can be written as
(1/2)^C(1) + (3/4){the original sequence}. Or, since C(1) = 2, S = 1/4
+ (3/4)S. Solving for S trivially gives S=1.
The key to this approach appears to be that by treating consecutive
pairs of the sequence as a unit (after the first) we get back a
multiple of the original sequence, much like solving an infinite
continuing fraction problem.
|
Posted by Paul
on 2005-08-20 20:32:01 |